Integrating ecological equivalence for native vegetation compensation: A methodological approach. (September 2021) - Mello, Kaline de; Fendrich, Arthur Nicolaus; Borges-Matos, Clarice; Brites, Alice Dantas; Tavares, Paulo André; da Rocha, Gustavo Casoni; Matsumoto, Marcelo; Rodrigues, Ricardo Ribeiro; Joly, Carlos Alfredo; Sparovek, Gerd; Metzger, Jean Paul
Abstract: Although offsetting schemes may avoid biodiversity loss, the implementation of these schemes can be challenging, given the difficulty of balancing biodiversity benefits with the resulting increase in compensation costs. Here we have developed a novel offsetting methodological approach to balance environmental gains and land availability to support the decision-making process and negotiations among stakeholders. We applied this approach for the compensation of Legal Reserves, a percentage of native vegetation area that landowners have to set apart in their rural properties in Brazil to maintain native vegetation. If landowners do not reach the Legal Reserves requirements on their land according to the law, they may compensate it in other equivalent properties. To balance environmental gains and land availability, we have developed a dynamic tool that allows users to objectively analyze results from multiple offsetting scenarios. These scenarios can combine different levels of abiotic and biotic equivalence requirements, along with the possibility of trading up, i.e . compensating in priority natural vegetation areas and/or priority areas for restoration, even without high equivalence, with the resulting balance on land availability. The proposed approach seeks to find acceptable solutions, balancing stakeholder requirements for ecological equivalence, land availability, and possibilities of trading up. This procedure can enhance the local trade of Legal Reserves compensation, minimizing biodiversity losses, and also reducing costs. Our case study shows that it is possible to apply ecological equivalence in a balanced manner for Legal Reserve compensation. Owing to its flexibility, the proposed approach and tool can be easily adopted by other compensation schemes worldwide, supporting the negotiation and decision-making processes, to reduce biodiversity loss. Highlights: We developed a dynamic decision support tool for native vegetation compensation. Our method allows balancing environmental and economic aspects in offset schemes. Our method allows the inclusion of trading up for areas with high ecological value. The method also includes the possibility of degraded pasturelands restoration. It is possible to apply ecological equivalence for Legal Reserves compensation.